Expansion and Contraction of the Indo-Pacific Tropical Rain Belt over the Last Three Millennia - Denniston, Rhawn F. (Sci Rep, 2016)
The seasonal north-south migration of the intertropical convergence zone (ITCZ) defines the tropical rain belt (TRB), a region of enormous terrestrial and marine biodiversity and home to 40% of people on Earth. The TRB is dynamic and has been shown to shift south as a coherent system during periods of Northern Hemisphere cooling. However, recent studies of Indo-Pacific hydroclimate suggest that during the Little Ice Age (LIA; AD 1400–1850), the TRB in this region contracted rather than being displaced uniformly southward. This behaviour is not well understood, particularly during climatic fluctuations less pronounced than those of the LIA, the largest centennial-scale cool period of the last millennium. Here we show that the Indo-Pacific TRB expanded and contracted numerous times over multi-decadal to centennial scales during the last 3,000 yr. By integrating precisely-dated stalagmite records of tropical hydroclimate from southern China with a newly enhanced stalagmite time series from northern Australia, our study reveals a previously unidentified coherence between the austral and boreal summer monsoon. State-of-the-art climate model simulations of the last millennium suggest these are linked to changes in the structure of the regional manifestation of the atmosphere’s meridional circulation.